TRAINING AND ASSISTANCE IN THE PREPARATION OF TEACHING MODULES FOR TEACHERS OF AISYIYAH MUHAMMADIYAH 3 JUNIOR HIGH SCHOOL - Andalas, Eggy Fajar; Asrini, Hari Windu; Fauzan, Fauzan (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Even though the government stipulates that the implementation of the Independent Curriculum is carried out in stages according to the readiness of each school, as one of the strategic national education policies, all schools are directed to be able to implement this curriculum. Based on initial observations, it was found that SMP Aisyiyah Muhammadiyah 3 Malang City needed training related to the Independent Curriculum as a form of preparation and to strengthen the competence of teachers. This is because even though they already know how to prepare teaching modules, they still find it difficult to design innovative teaching modules. To face this challenge, training and assistance are needed to strengthen understanding of the paradigm regarding the Independent Curriculum, which is integrated into the 21st-century learning paradigm and learning tools. This service aims to provide training and assistance in preparing the Independent Curriculum Teaching Module for teachers at Aisyiyah Muhammadiyah 3 Middle School, Malang City. The service uses a 4-stage creative process method: preparation, incubation, illumination, and verification. Based on the activities that have been carried out, one of the problems in the preparation was found, namely a knowledge deficit regarding various innovative learning designs and their implementation in the form of learning designs contained in teaching modules. Satisfying results were obtained through intensive training and mentoring. Teachers can create modules that meet minimum criteria and integrate innovative learning designs.